Eye movements in mild traumatic brain injury: Clinical challenges - Matthew A. McDonald; Helen V Danesh-Meyer; Samantha Holdsworth (Bern Open Publishing, 2022)
Mild traumatic brain injury (mTBI), also known as concussion, is a common injury which affects patients of all demographics. There is a global effort to accurately diagnose and identify patients at highest risk of prolonged symptom burden to facilitate appropriate rehabilitation efforts. Underreporting is common with large numbers not engaging with services, in addition to differences in treatment outcomes according to ethnicity, age, and gender. As patients recover, symptomology evolves which challenges rehabilitative efforts with no clear definition of 'recovered'. This review describes key areas in mTBI such as diagnostic challenges, epidemiology, prognosis, and pathophysiology which serves as an introduction to "Eye Movements in Mild Traumatic Brain Injury: Ocular Biomarkers."